Pengaruh Komunikasi Persuasif Akun TikTok @PandawaraGroup terhadap Peningkatan Minat Followers Melakukan Aksi Sosial - Pandu Sotyo Yugho Kuswanto; Sekartaji Anisa Putri (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
Environmental issues are becoming increasingly urgent, particularly the worsening clean water crisis, which requires effective mass communication to raise awareness and encourage community involvement. Social media has emerged as a strategic platform for disseminating information and promoting environmental actions. PandawaraGroup, a dedicated TikTok account focusing on environmental issues, utilizes persuasive communication to encourage positive actions. This study aims to examine the influence of persuasive communication by the @PandawaraGroup TikTok account on followers’ interest in participating in social actions. The research employed a quantitative method with data collected through an online questionnaire (Google Form) distributed to 100 respondents who are followers of the account. Data analysis was conducted using simple linear regression along with descriptive tests, validity, reliability, and dimensional analysis. The findings reveal that persuasive communication from @PandawaraGroup has a moderate influence on followers’ interest in engaging in social actions. Based on these results, the study suggests that @PandawaraGroup should strengthen follower engagement through active interactions, such as responding to comments and direct messages, as well as organizing regular Q&A or discussion sessions. Furthermore, diversifying content with creative approaches is essential to maintain audience interest and relevance. These strategies are expected to enhance the effectiveness of @PandawaraGroup in promoting environmental awareness and public participation.